Construction of Openness in the Context of Muhammadiyah Education: A Cultural Study Perspective - Hadirman, Hadirman; Ardianto, Ardianto; Bolotio, Rivai; Salim, Arhanuddin; Musafar, Musafar; Hardin, Hardin (IJBLE Scientific Publications Community Inc., 2024)
This research uses a cultural studies approach to describe the construction of openness in the context of Muhammadiyah education. Data were collected through observation, interviews, and document analysis through qualitative methods. The results show that openness in the Muhammadiyah educational environment involves accepting students from diverse cultural and religious backgrounds and practicing open dialogue and cooperation among all relevant parties. Additionally, this openness also includes acceptance of new ideas and values, recognition of differing perspectives, and the implementation of inclusive policies. This research aims to gain a deeper understanding of the development of openness in Muhammadiyah education from a cultural studies perspective and its impact in shaping an inclusive and responsive educational environment to cultural diversity.